A gyral coordinate system predictive of fibre orientations - Cottaar, Michiel; Bastiani, Matteo; Chen, Charles; Dikranian, Krikor; Van Essen, David; Behrens, Timothy E.; Sotiropoulos, Stamatios N.; Jbabdi, Saad (Elsevier, 2018)
When axonal fibres approach or leave the cortex, their trajectories tend to closely follow the cortical convolutions. To quantify this tendency, we propose a three-dimensional coordinate system based on the gyral geometry. For every voxel in the brain, we define a “radial” axis orthogonal to nearby surfaces, a “sulcal” axis along the sulcal depth gradient that preferentially points from deep white matter to the gyral crown, and a “gyral” axis aligned with the long axis of the gyrus.